1992
DOI: 10.1002/em.2850190305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotoxicity, pathological lesions, and cell proliferation in livers of rats and mice treated with furan

Abstract: Preliminary results from the National Toxicology Program (NTP) bioassays of furan given by gavage indicate the induction of hepatocellular carcinomas in male F-344 rats and in both sexes of B6C3F1 mice, and cholangiocarcinomas in both sexes of rats. To assess the genotoxicity of furan, chemically induced unscheduled DNA synthesis was evaluated in the in vivo hepatocyte DNA repair assay. Furan did not induce unscheduled DNA synthesis in hepatocytes isolated after single gavage treatment of male F-344 rats (5, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
0
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 42 publications
11
98
0
6
Order By: Relevance
“…7). As such the present data with coumarin are similar to those obtained in studies with furan (Wilson et al, 1992). Furan has been shown to produce hepatotoxic effects in the rat, a stimulation of hepatocyte labeling index values, and chronic administration results in hepatocellular adenomas/carcinomas and cholangiocarcinomas (Wilson et al, 1992).…”
Section: Weekssupporting
confidence: 87%
See 1 more Smart Citation
“…7). As such the present data with coumarin are similar to those obtained in studies with furan (Wilson et al, 1992). Furan has been shown to produce hepatotoxic effects in the rat, a stimulation of hepatocyte labeling index values, and chronic administration results in hepatocellular adenomas/carcinomas and cholangiocarcinomas (Wilson et al, 1992).…”
Section: Weekssupporting
confidence: 87%
“…The first class comprises mitogenic agents which produce additive hyperplasia with little or no toxicity, whereas the second class comprises cytotoxic agents where cell proliferation is the result of a regenerative hyperplasia (Loury et al, 1987;Goldsworthy et al, 1991;Grasso and Hinton, 1991;Ames et al, 1993). Examples of such rodent liver cytotoxic agents include carbon tetrachloride, chloroform, and furan (Loury et al, 1987;Grasso et al, 1991;Wilson et al, 1992;Larson et al, 1994).…”
Section: Weeksmentioning
confidence: 99%
“…This characteristic lesion is most likely to have resulted from direct diffusion of coumarin across the stomach wall, since the lobe or lobes affected were those in direct apposition to the serosal surface of the stomach. A similar lesion has been observed in rats and mice after oral dosing of another lipophillic substance, furan (Wilson et al, 1992), and has also been attributed to direct transgastric diffusion. Endell and Seidel (1978) showed that, following an oral dose of 350 mg/kg, C3H/He mice were more sensitive to coumarin hepatotoxicity than DBA/2 mice; however, these researchers were unable to demonstrate any strain difference after a lower dose of 250 mg/kg.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with the hypothesis that cytotoxicity mediated through binding of cis-2-butene-1,4-dial to critical target proteins is likely to play a key role in furan toxicity and carcinogenicity (Wilson et al, 1992), chemical characterization of furan metabolites in bile provided further evidence to suggest that degraded protein adducts are in vivo metabolites of furan. Based on our findings, however, we cannot conclude that the bile duct epithelium is a primary target of reactive furan metabolites, because biliary toxicity may also occur due to hepatocellular injury.…”
Section: Identification Of Furan-derived Metabolites In Rat Bilementioning
confidence: 53%